DANISH EXPERIENCE IN DIGITALIZATION OF BUSINESS PROCESSES AS AN EXAMPLE FOR UKRAINE - CHEREP, Alla; CHEREP, Oleksandr; OHRENYCH, Yuliia; KURCHENKO, Mykyta (Herald of Khmelnytskyi National University. Economic sciences, 2023)
As the world evolves, the impact of digitalization is becoming more and more pronounced. It is a tool that can be used to achieve positive results not only in the economy but also in other industries. Business digitalization is an advantage that maximizes profits and makes production more efficient. The article highlights the essence of digitalization and its benefits. The author's own interpretation of the concept of «digitalization» is provided and several definitions of this category from foreign researchers are considered. The authors analyze the digital economy of Denmark, its experience in digitalizing business processes and its place in the rankings of the digitization of the economy. The IMD World Digital Competitiveness Ranking 2023 and the Digital Economy and Society Index (DESI) are considered. The activities of the European company «Precis Digital» are analyzed. The leading countries in robotization of production are identified and Denmark's place in the installation of robots for 10 thousand employees is determined. The article compares Denmark and Ukraine in terms of digitalization, Internet connectivity and accessibility. It is found that Denmark ranks first in the European Union in terms of network connectivity. It is determined that the 5G network coverage in Denmark is significantly higher than the average for the European Union. The Danish Digital Growth Strategy is considered. The main initiatives of the Danish Strategy are analyzed. The Danish Recovery and Resilience Plan, which provides for investments and reforms aimed at expanding high-speed Internet access mainly in rural areas, is considered. The structure of enterprises in Denmark is considered. Digital public services in Ukraine and Denmark are studied. NemID, an electronic identification service in Denmark, and the DIIA («ДІЯ») application, a single portal for public services in Ukraine, are analyzed. Scenarios of digitalization development in Ukraine and its benefits are considered. It is determined that Denmark is the most digitized economy in Europe. The article develops recommendations for the digitalization of business processes in Ukraine based on the Danish experience.
Keywords: digitalization; digital transformation; business processes; information technology